2016 IEEE International Workshop on Electromagnetics: Applications and Student Innovation Competition (iWEM) 2016
DOI: 10.1109/iwem.2016.7504978
|View full text |Cite
|
Sign up to set email alerts
|

Partially-open SIW resonator for microwave characterization of particulate dielectrics: Effect of interaction with gases

Abstract: This work describes a novel measurement technique for determining the complex permittivity of powdered materials, based on resonant-perturbation of a Substrate Integrated Waveguide (SIW) resonator operating at ~2.5 GHz and calculations from General Dielectric Mixture Model equations. The proposed method is validated with standard powder samples measurement and comparison with the measured data by 3D electromagnetic simulation. The influence of the powder density is also discussed. The technique is then used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…To validate their dielectric sensitivity to humidity in test conditions, the dielectric constant of TOCN gels was tested under variable humidity conditions using the characterization method presented in [31].…”
Section: Rh-dependent Dielectric Characterization Of Tocnmentioning
confidence: 99%
See 1 more Smart Citation
“…To validate their dielectric sensitivity to humidity in test conditions, the dielectric constant of TOCN gels was tested under variable humidity conditions using the characterization method presented in [31].…”
Section: Rh-dependent Dielectric Characterization Of Tocnmentioning
confidence: 99%
“…The resonant frequency for each humidity level was measured and compared to the resonant frequency without TOCN. From the measured frequency shift, EM analyses were performed, and a calculation algorithm implementing the characterization method in [31] was applied to rigorously extract the values of the dielectric constant for each humidity level.…”
Section: Rh-dependent Dielectric Characterization Of Tocnmentioning
confidence: 99%
“…[10,11]. Several sensors are implemented using various techniques, including SIW [10][11][12][13][14][15][16][17]. However, these sensors are available in larger sizes due to the use of full-mode SIW technology.…”
Section: Introductionmentioning
confidence: 99%
“…Recently published articles have also demonstrated that SIW can be used for sensing applications. For example, SIW resonators have been used to detect or characterize a fluid in a system or to characterize materials [13]. To the best knowledge of the authors, no investigation of fully biodegradable materials for humidity sensing in passive microwave devices has been reported.…”
Section: Introductionmentioning
confidence: 99%